자원의 비효율적인 변동과 비용을 고려한 다중 자원 평준화 방법 - 이제섭; 장민서; 김호진; 이승우; 신도형; Rhie, Jeseop; Jang, Minseo; Kim, Hojin; Lee, Seungwoo; Shin, Do Hyoung (한국건설관리학회 논문집, 26(2), 2025)
In construction projects, inefficient resource fluctuations can lead to hiring, firing and rehiring of resources, or cause idle time, thereby incurring additional costs. Reducing such fluctuations is a critical task in resource leveling, and various studies have employed Release and Re-Hire (RRH) and Resource Idle Days (RID) as evaluation metrics. However, in multiple resources leveling, it is necessary to comprehensively consider both the inefficient fluctuations and costs of each resource, yet research in this area remains insufficient. This study proposes a cost-based multiple resources leveling model that applies weights according to the unit costs incurred by RRH or RID for each resource, aiming to reduce both RRH or RID and the associated costs simultaneously. To validate the model, the proposed model was applied to a cost-based multiple resources leveling system using a genetic algorithm, and multiple resources leveling was performed on a scheduling example with two types of resources, with different cost structures. By applying both RRH and RID, it was confirmed that the proposed model more effectively reduced loss costs compared to the existing model. This study presents a model that effectively reduces RRH or RID in projects with differing cost structures between resources, making a practical contribution to resource management in construction projects aimed at cost reduction. 건설 프로젝트에서 비효율적인 자원 변동(inefficient resource fluctuation)은 자원의 고용, 해고, 재고용을 유발하거나 자원의 유휴시간을 발생시켜 추가적인 비용을 초래할 수 있다. 이러한 변동을 줄이는 것은 자원 평준화에서 중요한 과제이며, 이를 평가하기 위한 Release and Re-Hire (RRH)와 Resource Idle Days (RID)를 활용한 다양한 연구가 진행되어 왔다. 그러나, 다중 자원 평준화에서는 각 자원의 비효율적인 변동과 비용을 종합적으로 고려해야 하며, 이에 대한 연구는 부족한 실정이다. 본 연구에서는 각 자원의 RRH 또는 RID로 인한 단위발생비용 가중치를 적용하여 RRH 또는 RID와 이로 인해 발생하는 비용을 동시에 줄이는 비용 기반 다중자원 평준화 모델을 제안하였다. 모델 검증을 위해, 유전 알고리즘을 활용한 비용 기반 다중 자원 평준화 시스템에 본 모델을 적용해, 비용 구조가 상이한 두 종류의 자원이 포함된 공정계획 예제에 대해 다중 자원 평준화를 실시하였다. RRH와 RID를 각각 적용한 결과, 제안 모델이 기존 모델에 비해 손실 비용을 더 효과적으로 감소시킴을 확인하였다. 본 연구는 자원 간 비용 구조가 상이한 프로젝트에서 RRH 또는 RID를 효과적으로 줄이는 모델을 제시하여, 비용 절감을 목표로 하는 건설 프로젝트의 자원 관리에 실질적인 기여를 할 수 있을 것이다.